Hubungan Minat dan Kepribadian Anak-anak dan Orang Dewasa dalam Pengilustrasian Animasi - Aura Amelia Ridlwan; Muhammad Fauzi (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Animation has transcended its traditional association with children’s entertainment and emerged as a dynamic global medium that resonates with audiences across age groups. Beyond its role as a form of visual amusement, animation demonstrates significant potential in conveying meaningful narratives and creating emotional engagement through carefully crafted aesthetic experiences. A central element in the animation process is character design, where the combination of shape, color, and expression not only determines visual appeal but also functions as a medium for reflecting personality and emotional depth. This study aims to investigate the relationship between personal interests and personality traits in shaping visual preferences toward animation illustrations among children and adults. Through a literature review, the research highlights how individual interests—deeply influenced by developmental needs, social environment, and past experiences—play a crucial role in guiding aesthetic choices. Findings suggest that children are typically drawn to characters with simplified forms, bright and saturated colors, and exaggerated expressions that facilitate recognition, comprehension, and emotional connection. Conversely, adults tend to prefer more complex designs, incorporating nuanced emotional cues, realistic proportions, and layered symbolism that align with mature cognitive and emotional processing. The comparison underscores the importance of audience segmentation in animation design, particularly in creating characters that are not only visually engaging but also resonate with psychological and emotional expectations. By recognizing and addressing the distinct preferences of different age groups, animators and illustrators can develop content that is more contextually relevant, immersive, and capable of fostering long-term audience attachment. Ultimately, this study emphasizes that effective animation character design extends beyond technical artistry; it requires a deep understanding of human psychology, cultural influences, and the evolving nature of visual engagement across the lifespan.